Civil Wars in South Asia : State, Sovereignty, Development - Edited by Sundar, Aparna; Sundar, Nandini (Los Angles SAGE Publications India Pvt Ltd., 2014)
Scrutinizes the questions of sovereignty, citizenship, state contours in the South Asia region!
Include Index
Keywords: South Asia -- Politics and government -- Social conflict